The Sense of Agency of Virtual Hand Representation for Online Shopping - Abdul Rahim, Nurul Aiman; Norasikin, Mohd Adili (2020)
The advancement of virtual reality technology has made real-life manipulation possible in virtual environment since there is a feeling of control, also known as the sense of agency. However, to create a greater virtual experience (e.g., perception of size) of a real-world model (e.g., smartphone) with its model representation in digital or virtual environment (VE) is difficult. For example, the representation model (e.g., in an online shopping website) might visually differ in size compared to the physical world. This study addresses the problem by introducing a calibration method to best match the ratio of virtual hand representation with its associated object in VE and in the real world. This project creates a prototype made by off the shelf motion sensor (i.e., Leap Motion) and Unity software. User can virtually inspect online products as if he is holding the product in the real world. This study evaluates the sense of agency by comparing experience of participants before and after using the proposed prototype. Results showed that the sense of agency is much higher in the proposed method compared to conventional online shopping (i.e., no virtual inspection).